2015
DOI: 10.1027/1015-5759/a000198
|View full text |Cite
|
Sign up to set email alerts
|

Differential Item Functioning by Education and Sex in Subtests of the Repeatable Battery Assessment of Neuropsychological Status

Abstract: The main objective of this study is to evaluate functions of the items changing with the gender and educational level in the List Learning and the Picture Naming subtests in the Repeatable Battery Assessment of Neuropsychological Status. The study was implemented on 315 volunteers consisting of 157 women and 158 males in the 20–79 age group with three different educational levels (107 graduates of primary school, 102 graduates of high school, and 106 graduates of university). Logistic Regression method was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“… 31 To the best of our knowledge, no previous reports have found an influence of sex on DIF in the BNT. However, one study found an influence of sex on DIF in the Picture Naming in Repeatable Battery Assessment of Neuropsychological Status (RBANS), 32 which suggests that sex is a potential confounding factor in the current study. The only method we know to control for confounding in DIF analyses based on IRT is matching; however, we were unable to match samples in the current study due to our limited sample size.…”
Section: Discussionmentioning
confidence: 63%
“… 31 To the best of our knowledge, no previous reports have found an influence of sex on DIF in the BNT. However, one study found an influence of sex on DIF in the Picture Naming in Repeatable Battery Assessment of Neuropsychological Status (RBANS), 32 which suggests that sex is a potential confounding factor in the current study. The only method we know to control for confounding in DIF analyses based on IRT is matching; however, we were unable to match samples in the current study due to our limited sample size.…”
Section: Discussionmentioning
confidence: 63%
“…The standardization study involved 315 healthy individuals (157 females and 158 males) aged 20-79 years. Educational background of the participants is characterized as follows: 107 participants graduated from elementary school, 102 from high school, and 106 from university 11 .…”
Section: Participantsmentioning
confidence: 99%